Congruence of Competitive Advantage and Transfer Pricing: A Study on Selected MNCs Operating in Bangladesh - Siddique, Md. Nur-E-Alam; Ahmed, Alim Al Ayub (Asian Accounting and Auditing Advancement, 2019)
For many years transfer pricing has been considered an adherence issue whereby MNCs are lawfully required to arrange, document, and file with tax revenue authorities. Moreover, most researchers have written on the economics, accounting, taxation, and finance aspect of transfer pricing. But, later, transfer pricing has been recognized as a strategic tool that can facilitate MNCs to achieve competitive advantage. Furthermore, there are few kinds of literature on transfer pricing and strategy. The study’s research question was to find out how MNCs operating in Bangladesh are applying transfer pricing as a strategic tool. The study adopted a descriptive research design which enabled the description of characteristics connected with the subject population. It was found that transfer pricing was practiced to achieve internal objectives such as motivating subsidiary managers, monitoring the performance of foreign subsidiaries, and as a way of achieving goal synchronization between subsidiary managers and parent companies. External objectives incorporated the practice of transfer pricing as a means of reducing taxes and duties as a tool of controlling foreign exchange risks, as a cash management means, and as a way of evasion foreign government interference. It was discovered that in contrast to pure accounting, economics, and tax-driven systems, transfer pricing is viewed as a tool for advancing MNC strategies in Bangladesh. Findings pointed out that executives were not exclusively focused on compliance, accounting, economics, and taxation issues as primary objectives of transfer pricing.